Preparation method of fluorine-containing biochar composite material and application of fluorine-containing biochar composite material as energy storage electrode in supercapacitor
A hierarchical porous fluorinated biochar composite material was prepared by coating the surface of biochar with fluorinated carbon (fluorinated pitch) using a high-temperature vacuum evaporation method. This solved the problem of insufficient energy density in supercapacitor electrode materials and enabled the preparation of high-performance electrode materials and the resource utilization of agricultural waste.
Patent Information
- Application Number
- CN202511659024.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-13
- Publication Date
- 2026-02-17
AI Technical Summary
Existing supercapacitor electrode materials have insufficient energy density, and traditional modification techniques such as KOH activation have limited effect on improving conductivity. Carbon nanotube composites are too expensive and cannot meet the requirements for high-performance energy storage.
A hierarchical porous fluorinated biochar composite material was prepared by coating biochar with fluorinated carbon (fluorinated pitch) using a high-temperature vacuum evaporation method, which improved the electrochemical stability and charge storage efficiency of the electrode material.
The prepared electrode material exhibits high specific surface area, abundant surface functional groups, and excellent electrochemical performance, which improves the energy density and cycle stability of supercapacitors and realizes the resource utilization of agricultural waste.
Smart Images

Figure CN121545928A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of biochar energy storage material preparation, and particularly relates to a preparation method of fluorine-containing biochar composite material and application of the fluorine-containing biochar composite material as an energy storage electrode in a supercapacitor. BACKGROUND
[0002] At present and in a long period of time in the future, global energy demand still mainly relies on fossil fuels, but the limited reserves and the environmental problems caused in the process of exploitation and use of fossil fuels have attracted much attention. The use of renewable energy such as solar energy, wind energy, tidal energy and bioenergy has become the focus, but there are problems of energy storage, output instability and intermittency in the process of development of these energies, which are difficult to meet the actual demand. Therefore, energy storage has become a necessary link for the use of new energy. The conversion of renewable energy into electrical energy and the realization of efficient storage and stable supply through a large-capacity energy storage system can balance the contradiction between energy demand and sustainable development.
[0003] Supercapacitors have become important energy storage devices due to their high power density, fast charging and discharging capability and long cycle life, but the insufficient energy density limits the application expansion. Among the influencing factors, the performance of electrode materials is the key influencing factor. Compared with traditional natural graphite and carbon materials carbonized from fossil fuels, biomass-derived carbon is widely concerned due to its wide raw materials, low cost, strong environmental compatibility and renewability. Through precise carbonization and activation process, the biochar with multi-level pore structure can significantly improve the charge storage efficiency and charge capacity. However, the original biomass carbon generally has defects such as low porosity, small specific surface area and insufficient specific capacitance, which restricts the energy storage performance. Current research focuses on developing biomass carbon electrode materials with high porosity, high conductivity and adjustable structure to synergistically improve the energy density and power density and break through the technical bottleneck of supercapacitors.
[0004] Corn is one of the main food crops in the world, and its byproduct corn cob has a huge yield but low utilization rate. Converting corn cob into high-performance biochar can not only realize the resource utilization of agricultural waste, but also reduce environmental pollution, which is in line with the concept of sustainable development. SUMMARY
[0005] The application aims to provide a preparation method and application of carbon fluoride / fluorinated pitch coated corncob hierarchical porous biochar composite material. The preparation method provided by the application is simple and easy to operate. The prepared corncob hierarchical porous biochar composite material has high specific surface area, hierarchical porous structure and rich surface functional groups, and exhibits excellent electrochemical performance. On one hand, the coating can effectively improve the surface properties of the biochar, improve the compatibility of the biochar with the electrolyte, and promote the transmission and adsorption of ions; on the other hand, the fluorine element in the carbon fluoride and the fluorinated pitch can endow the electrode material with higher electrochemical stability and unique electrochemical activity, thereby improving the energy density and cycle stability of the supercapacitor. From the future development trend, with the increasing requirement for the performance of the supercapacitor, the carbon fluoride / fluorinated pitch coated corncob-based biochar electrode material has a broad development prospect in the field of supercapacitors.
[0006] To achieve the above-mentioned purposes, the technical scheme adopted by the application is as follows: In a first aspect, the application provides a preparation method of a fluorine-containing biochar composite material, comprising the following steps: (1) pretreating the corncob raw material, cutting the corncob into small pieces, performing ultrasonic cleaning, then drying, crushing, passing through a 100-mesh screen, and obtaining corncob powder through sieving; (2) performing high-temperature pre-carbonization on the corncob powder obtained in step (1), and taking out after cooling, to obtain corncob biochar; (3) fully grinding and mixing the corncob biochar in step (2) with KOH in a certain proportion, performing high-temperature activation, and taking out after cooling; the obtained biochar material is first neutralized to neutral, then repeatedly washed, and finally dried to obtain a corncob hierarchical porous carbon material; (4) fluorinating a certain amount of fluoride and coating it on the surface of the corncob hierarchical porous carbon material to obtain a fluorine-containing biochar composite material.
[0007] Preferably, the ultrasonic cleaning power in step (1) is 432 W, and the cleaning time is 20 min.
[0008] Preferably, the pre-carbonization conditions in step (2) are as follows: the heating rate is 1-15 ℃ / min, the pre-carbonization temperature is 600-800 ℃, and the pre-carbonization time is 30-120 min.
[0009] Preferably, the mass ratio of KOH to corncob biochar in step (3) is 0.3-3:1.
[0010] Preferably, the activation conditions in step (3) are as follows: the heating rate is 1-15 ℃ / min, the activation temperature is 550-850 ℃, and the activation time is 30-120 min.
[0011] Preferably, the fluoride in step (4) of the present application is fluorinated carbon and / or fluorinated pitch, and the fluorination conditions are: a fluorination temperature of 380-758 ℃, and a fluorination time of 5-20 min. Preferably, the mass ratio of the corncob hierarchical porous carbon material to the fluoride in the present application is 1~1.9:1.
[0012] In a second aspect, the present application provides a fluorine-containing biochar composite material prepared by the preparation method of the first aspect.
[0013] In a third aspect, the present application provides a preparation method of an electrode material, comprising the following steps: The fluorine-containing biochar composite material, acetylene black and polyvinylidene fluoride solution are weighed in a mass ratio of 8:1:1, the fluorine-containing biochar composite material and acetylene black are added to anhydrous ethanol and ultrasonically mixed, then the PVDF solution is added and ultrasonically mixed, then the sample sheet is dropped and coated on the foamed nickel, the sample sheet is dried and then pressed into a uniform and flat sheet, and finally an electrode with a mass ratio of the fluorine-containing biochar composite material of 80% is prepared.
[0014] Preferably, the polyvinylidene fluoride solution refers to polyvinylidene fluoride fully dissolved in N-methylpyrrolidone.
[0015] In a fourth aspect, the present application provides an electrode prepared by the preparation method of the third aspect.
[0016] In a fifth aspect, the present application provides an application of the electrode material, wherein the electrode of the fourth aspect is used as a working electrode to construct a supercapacitor.
[0017] Compared with the prior art, the present application has the following beneficial effects: 1) The present application provides a new way for high-value utilization of agricultural waste: the electrode material of the present application uses corncob as raw material, which is widely available and low in cost, and the corncob is converted into high-performance biochar, which not only realizes the resource utilization of agricultural waste, but also reduces environmental pollution, and conforms to the concept of sustainable development. The obtained corncob biochar has high specific surface area, hierarchical porous structure and rich surface functional groups, which can effectively improve the capacitance performance of the supercapacitor electrode material, and has great application value; 2) Technical innovation of high-temperature vacuum evaporation of fluorinated carbon (fluorinated pitch): The existing modification technology has limitations (such as KOH activation method has limited improvement on electrical conductivity, and the cost of carbon nanotube (CNT) composite is too high). The preparation process of the present application is simple. The surface of biochar is coated with fluorinated carbon (fluorinated pitch) by high-temperature vacuum evaporation method. The gaseous fluorinated carbon (fluorinated pitch) is rapidly condensed and coated on the surface of biochar in the condenser tube by desublimation, and a fluorinated carbon-coated biochar composite material is obtained. The electrode material prepared from the biochar composite material has good electron transfer ability and hierarchical porous structure, and has excellent electrochemical performance, which can be used in the field of supercapacitors.
[0018] 3) Excellent electrochemical performance: Experimental tests prove that the corn cob hierarchical porous carbon composite material prepared by the method of the present application has an average specific capacitance of 356 F·g -1 at a current density of 0.5 A·g -1 -1 in a three-electrode system, an energy density of 105.91 Wh·kg -1 at a low power density of 381.26 W·kg -1 -1, and an energy density of about 26.63 Wh·kg -1 at a power density of 15.8 kW·kg -1 -1; the fluorinated pitch-coated sample has an average specific capacitance of 367 F·g -1 at 0.5 A·g -1 -1, an energy density of 93.25 Wh·kg -1 at a low power density of 335.7 W·kg -1 -1, and an energy density of about 29.43 Wh·kg -1 at a power density of 13.05 kW·kg -1 -1. It shows excellent electrochemical performance. BRIEF DESCRIPTION OF DRAWINGS
[0019] Figure 1 is a preparation flow chart of the corn cob hierarchical porous carbon composite material; Figure 2 is a SEM image of the corn cob hierarchical porous carbon composite material, wherein (a) is a SEM image of the fluorinated carbon-coated corn cob hierarchical porous carbon composite material CHPC-CF X 1:1 in Example 1, and (b) is a SEM image of the fluorinated pitch-coated corn cob hierarchical porous carbon composite material CHPC-IPF1:1 in Example 1; Figure 3 is a corn cob hierarchical porous carbon composite material CHPC-CF XCV curves, GCD curves, Nyquist plots, and CHPC-CF X Specific capacitance plots at different current densities; Figure 4 The CV curves, GCD curves, Nyquist plots, and specific capacitance plots of CHPC-IPF at different current densities are shown for the corn cob graded porous carbon composite materials CHPC-IPF prepared in Examples 1-5. Detailed Implementation
[0020] The present invention will be further described in detail below with reference to examples. Examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention. Any changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention should be considered equivalent substitutions and are included within the protection scope of the present invention. Equivalent techniques of the specific embodiments described that can be understood by those skilled in the art through conventional experimentation are included in this application. Example 1
[0021] like Figure 1 As shown, the preparation method of the fluorinated carbon / fluorinated pitch coated corn cob graded porous carbon composite material of the present invention includes the following steps: (1) Pre-treatment of corn cob raw materials: cut corn cob into small pieces, use a mixture of deionized water and anhydrous ethanol for ultrasonic cleaning (ultrasonic cleaning power: 432 W, cleaning time: 20 min) to remove surface impurities, then place in an 80 ℃ oven to dry for 24 h, then crush with a multi-functional pulverizer, pass through a 100 mesh sieve, obtain sample powder by sieving, dry and store for later use; (2) Place the corn cob powder obtained in step (1) into a covered corundum crucible, and use the sand-burying and sealing method to place it in a muffle furnace for high-temperature pre-carbonization. The pre-carbonization conditions are: heating rate of 5℃ / min, pre-carbonization temperature of 800℃, and pre-carbonization time of 120min. After the pre-carbonization is completed, take it out after cooling to room temperature with the furnace to obtain corn cob biochar. (3) Weigh 24 g of KOH and 8 g of corn cob biochar from step (2) and grind them thoroughly in a mortar at a ratio of 3:1. Activate the mixture at high temperature in a muffle furnace. The activation conditions are: heating rate of 5 ℃ / min, activation temperature of 850 ℃, and activation time of 120 min. After activation, cool the mixture to room temperature in the furnace and remove it. The obtained biochar material is first washed with 2 M HCl, then washed with deionized water until the pH of the filtrate is neutral. Finally, dry it at a constant temperature of 80 ℃ for 24 h to obtain graded porous corn cob carbon material. (4) Weigh 0.5 g of fluorinated carbon (fluorinated pitch) and place it in a quartz bottle. Weigh 0.5 g of the prepared corn cob graded porous carbon and place it evenly in the four bulbs of the condenser. Heat the quartz bottle with an alcohol torch and fluorinate it at a certain temperature. The fluorination conditions are: fluorination temperature of the fluorinated carbon composite material is 658 ℃ and fluorination time is 20 min; fluorination temperature of the fluorinated pitch composite material is 439 ℃ and fluorination time is 20 min. The gaseous fluorinated carbon / fluorinated pitch is rapidly condensed and coated on the surface of the biochar in the condenser. The resulting fluorinated carbon-coated corn cob graded porous carbon composite material is labeled as CHPC-CF. X The 1:1 fluorinated bitumen-coated corn cob graded porous carbon composite material is labeled CHPC-IPF1:1.
[0022] SEM image of corn cob graded porous carbon composite material as shown below Figure 2 As shown, by Figure 2 As shown in (a), the smooth, layered fluorinated carbon, after being vaporized by high-temperature vacuum evaporation, breaks down into layered spheres and fluorinated carbon particles of varying sizes. These spheres and particles form a tight network covering the biochar surface, increasing the number of active sites at the material's edges. This makes the material more readily interact with the electrolyte in electrochemical reactions, promoting ion adsorption and deintercalation, and ultimately improving electrochemical performance. Figure 2 As shown in (b), after high-temperature vaporization, the originally rough fluorinated asphalt particles break down into smooth particles of varying shapes and sizes. These smooth fluorinated carbon particles then rapidly condense and coat the biochar surface via sublimation in the condenser. The smooth coating of the fluorinated asphalt makes it easier for the electrolyte to wet, increasing the contact area for the electrochemical reaction. This structural difference further reduces the internal resistance of the material and improves the electron conduction path. This structural difference allows the fluorinated asphalt-coated sample to maintain the ion diffusion path more stably during charge and discharge. Based on CHPC-CF X1:1 (CHPC-IPF1:1) Method for preparing electrode material, 0.04 g of the above-mentioned corncob hierarchical porous carbon composite material, 0.005 g of acetylene black and 0.005 g of polyvinylidene fluoride (PVDF) are weighed in a mass ratio of 8:1:1, 0.005 g of PVDF is dissolved in 2 ml of N-methyl pyrrolidone (NMP), and stirred until a transparent liquid is obtained for standby. Then, the composite material sample and acetylene black are added to a proper amount of anhydrous ethanol and ultrasonically mixed for 40 min, then the PVDF solution is added and ultrasonically mixed for another 40 min to form a slurry with certain fluidity and stability, which is then dropped onto a foam nickel with a size of about 10*20 mm, and the sample sheet is placed in an oven at 105 ℃ for drying for 12 h, after which it is taken out and pressed into a uniform flat sheet using a powder tablet press under a pressure of 1 MPa, and finally a working electrode is prepared, which is an electrode with a mass ratio of corncob hierarchical porous carbon composite material of 80%.
[0023] In this embodiment, the Autolab electrochemical workstation of Swiss Watan was used for electrochemical performance test of the electrode material. In a typical three-electrode test system, the prepared carbon fluoride / flourine pitch coated composite material was used as the working electrode, the Hg / HgO electrode was used as the reference electrode, the platinum electrode was used as the counter electrode, and the 6 mol / L KOH solution was used as the electrolyte.
[0024] CHPC-CF X The test results of the 1:1 electrode sheet are as follows: the specific surface area is 1200.64 m 2 ·g -1 ; the total pore volume is 0.75 cm 3 ·g -1 ; the specific capacitance is 309.93 F·g -1 at a current density of 0.5 A·g -1 , the energy density of the sample reaches 94.36 Wh·kg -1 at a low power density of 370.15 W·kg -1 , the energy density remains at about 17.76 Wh·kg -1 when the power density reaches 15.75 kW·kg -1 .
[0025] The test results of the CHPC-IPF1:1 electrode sheet are as follows: the specific surface area is 2858.04 m 2 ·g -1 ; the total pore volume is 1.59 cm 3 ·g -1 ; the specific capacitance is 356.53 F·g -1 at a current density of 0.5 A·g .-1 At a low power density of 350.60 W·kg -1 The energy density of the sample reached 97.39 Wh·kg⁻¹. -1 With a power density of 15.38 kW·kg -1 At that time, the energy density remained at 20.08 Wh·kg -1 about. Example 2
[0026] In step (4) of Example 1, 0.65 g of the prepared corn cob graded porous carbon was weighed out, and the remaining steps remained unchanged. The resulting fluorinated carbon-coated corn cob graded porous carbon composite material was labeled CHPC-CF. X The 1.3:1 fluorinated asphalt-coated corn cob graded porous carbon composite material is labeled CHPC-IPF1.3:1.
[0027] CHPC-CF X The test results for the 1.3:1 electrode sheet are as follows: specific surface area is 1201.46 m². 2 ·g -1 The total pore volume is 0.74 cm³. 3 ·g -1 ; at 0.5 A·g -1 At a current density of , the specific capacitance is 412.74 F·g. -1 At a low power density of 302.85 W·kg -1 The energy density of the sample reached 84.12 Wh·kg⁻¹. -1 With a power density of 15.43 kW·kg -1 At that time, the energy density remained at 13.72 Wh·kg -1 about.
[0028] The test results for the CHPC-IPF1.3:1 electrode sheet are as follows: specific surface area is 2654.41 m². 2 ·g -1 The total pore volume is 1.50 cm³. 3 ·g -1 ; at 0.5 A·g -1 At a current density of , the specific capacitance is 421.82 F·g. -1 At a low power density of 296.33 W·kg -1 The energy density of the sample reached 82.31 Wh·kg⁻¹. -1 With a power density of 11.34 kW·kg -1 At that time, the energy density remained at 12.50 Wh·kg -1 about. Example 3
[0029] In step (4) of Example 1, 0.75 g of the prepared corn cob graded porous carbon was weighed out, and the remaining steps remained unchanged. The resulting fluorinated carbon-coated corn cob graded porous carbon composite material was labeled CHPC-CF. X The 1.5:1 fluorinated asphalt-coated corn cob graded porous carbon composite material is labeled CHPC-IPF1.5:1.
[0030] CHPC-CF X The test results for the 1.5:1 electrode sheet are as follows: specific surface area is 1204.06 m². 2 ·g -1 The total pore volume is 0.75 cm³. 3 ·g -1 ; at 0.5 A·g -1 At a current density of , the specific capacitance is 392.61 F·g. -1 At a low power density of 318.38 W·kg -1 The energy density of the sample reached 88.44 Wh·kg⁻¹. -1 With a power density of 10.7 kW·kg -1 At that time, the energy density remained at 11.77 Wh·kg -1 about.
[0031] The test results for the CHPC-IPF1.5:1 electrode sheet are as follows: specific surface area is 2575.59 m². 2 ·g -1 The total pore volume is 1.45 cm³. 3 ·g -1 ; at 0.5 A·g -1 At a current density of , the specific capacitance is 348.49 F·g. -1 At a low power density of 358.69 W·kg -1 The energy density of the sample reached 99.63 Wh·kg⁻¹. -1 With a power density of 11.5 kW·kg -1 At that time, the energy density remained at 20.29 Wh·kg -1 about. Example 4
[0032] In step (4) of Example 1, 0.85 g of the prepared corn cob graded porous carbon was weighed out, and the remaining steps remained unchanged. The resulting fluorinated carbon-coated corn cob graded porous carbon composite material was labeled CHPC-CF. X The 1.7:1 ratio of fluorinated asphalt-coated corn cob graded porous carbon composite material is designated as CHPC-IPF1.7:1.
[0033] CHPC-CFX The test results for the 1.7:1 electrode sheet are as follows: specific surface area is 1699.71 m². 2 ·g -1 The total pore volume is 1.04 cm³. 3 ·g -1 ; at 0.5 A·g -1 At a current density of , the specific capacitance is 327.85 F·g. -1 At a low power density of 381.26 W·kg -1 The energy density of the sample reached 105.91 Wh·kg⁻¹. -1 With a power density of 15.77 kW·kg -1 At that time, the energy density remained at 26.63 Wh·kg -1 about.
[0034] The test results for the CHPC-IPF1.7:1 electrode sheet are as follows: specific surface area is 2457.11 m². 2 ·g -1 The total pore volume is 1.41 cm³. 3 ·g -1 ; at 0.5 A·g -1 At a current density of , the specific capacitance is 372.35 F·g. -1 At a low power density of 335.70 W·kg -1 The energy density of the sample reached 93.25 Wh·kg⁻¹. -1 With a power density of 13.01 kW·kg -1 At that time, the energy density remained at 29.43 Wh·kg -1 about. Example 5
[0035] In step (4) of Example 1, 0.95 g of the prepared corn cob graded porous carbon was weighed out, and the remaining steps remained unchanged. The resulting fluorinated carbon-coated corn cob graded porous carbon composite material was labeled CHPC-CF. X The 1.9:1 ratio of fluorinated asphalt-coated corn cob graded porous carbon composite material is designated as CHPC-IPF1.9:1.
[0036] CHPC-CF X The test results for the 1.9:1 electrode sheet are as follows: specific surface area is 1844.18 m². 2 ·g -1 The total pore volume is 1.07 cm³. 3 ·g -1 ; at 0.5 A·g -1 At a current density of , the specific capacitance is 336.91 F·g. -1At a low power density of 371.01 W·kg -1 The energy density of the sample reached 103.06 Wh·kg⁻¹. -1 With a power density of 16.52 kW·kg -1 At that time, the energy density remained at 11.11 Wh·kg -1 about.
[0037] The test results for the CHPC-IPF1.9:1 electrode sheet are as follows: specific surface area is 1645.98 m². 2 ·g -1 The total pore volume is 0.92 cm³. 3 ·g -1 ; at 0.5 A·g -1 At a current density of , the specific capacitance is 341.49 F·g. -1 At a low power density of 366.04 W·kg -1 The energy density of the sample reached 101.68 Wh·kg⁻¹. -1 With a power density of 15.35 kW·kg -1 At that time, the energy density remained at 15.9 Wh·kg -1 about.
[0038] The pore structure parameters of the corn cob graded porous carbon composite materials prepared in Examples 1-5 are shown in Tables 1 and 2.
[0039] Table 1 CHPC-CF X Hole structure parameters Samples S BET (m 2 g -1 )]]> S micro (m 2 g -1 )]]> S meso and S macro (m 2 g -1 )]]> V total (cm 3 g -1 )]]> V micro (cm 3 g -1 )]]> D ave (nm)]]> CHPC-CF X 1:1]]> 1200.64 857.11 401.78 0.75 0.5518 2.059 CHPC-CF X 1.3:1]]> 1201.46 891.50 388.59 0.74 0.5512 2.040 CHPC-CF X 1.5:1]]> 1204.06 889.58 388.60 0.75 0.5533 2.046 CHPC-CF X 1.7:1]]> 1699.71 1260.52 533.62 1.04 0.7817 2.030 CHPC-CF X 1.9:1]]> 1844.18 1476.04 514.43 1.07 0.8531 2.157 Table 2 Pore structure parameters of CHPC-IPF Samples S BET (m 2 g -1 )]]> S micro (m 2 g -1 )]]> S meso and S macro (m 2 g -1 )]]> V total (cm 3 g -1 )]]> V micro (cm 3 g -1 )]]> D ave (nm) CHPC-IPF 1 : 1 2858.04 2239.17 855.41 1.59 1.31 2.019 CHPC-IPF 1.3: 1 2654.41 2073.71 828.89 1.50 1.25 2.142 CHPC-IPF 1.5: 1 2575.59 2038.09 791.39 1.45 1.21 2.129 CHPC-IPF 1.7: 1 2457.11 1909.74 753.97 1.41 1.16 2.01 CHPC-IPF 1.9: 1 1645.98 1382.38 344.57 0.92 0.79 2.05 The corn cob hierarchical porous carbon composite material CHPC-CF prepared in Examples 1-5 X CV curves, GCD curves, Nyquist plots, and CHPC-CF X The specific capacitance diagrams at different current densities are as follows: Figure 3 As shown, Figure 3 As shown in (a), after the biochar surface was coated with fluorinated carbon, the redox peaks that originally belonged to pure fluorinated carbon were significantly weakened, CHPC-CF X The CV curve is roughly rectangular, exhibiting typical characteristics of electric double-layer capacitance (EDLC). Furthermore, the CV curve shows weak oxidation and reduction peaks, indicating the presence of pseudocapacitance caused by the Faraday reaction in the coating material.
[0040] CHPC-CF X The galvanostatic charge-discharge (GCD) curve of the material is as follows:Figure 3 As shown in (b), it can be seen that within the potential window range of -1.2 V to 0.6 V, 0.5 A g -1 At the given current density, the charge-discharge curve is not ideally linear, which further confirms that a Faraday reaction occurs during these processes.
[0041] Figure 3 (c) is the composite material CHPC-CF X The Nyquist plot shows a near-linear shape in the low-frequency region, reflecting the electric double-layer characteristics. The semi-circular diameter in the high-frequency region is related to the sample's charge transfer resistance (Ro). ct The intercept of the curve on the real axis represents the equivalent series resistance (R). s ). Among them, CHPC-CF was analyzed. X From the Nyquist plot with a ratio of 1.7:1, we can obtain its R... ct and R s The lower the resistance, the stronger the conductivity of the sample, which can effectively promote rapid charge transfer.
[0042] exist Figure 3 As can be seen in (d), the specific capacitance of the sample generally decreases with increasing current density, which is attributed to the resistance at higher discharge current densities and the insufficiency of the Faraday redox reaction. Specifically, at 0.5 A·g... -1 At that time, CHPC-CF X The specific capacitance of the 1.7:1 material can reach 327.85 F·g. -1 In 20 A·g -1 At high current densities, CHPC-CF X The specific capacitance of the 1.7:1 material can still be maintained at 77.12 F·g. -1 .
[0043] The CV curves, GCD curves, Nyquist plots, and specific capacitance plots of the corn cob graded porous carbon composite material CHPC-IPF prepared in Examples 1-5 are shown below. Figure 4 As shown. By Figure 4 As shown in (a), the CV curve of the composite material (CHPC-IPF) is roughly rectangular, reflecting the typical characteristics of electric double-layer capacitance (EDLC). The CV curve of the CHPC-IPF coating material exhibits weak oxidation and reduction peaks around 0.44–0.46 V and 0.22–0.25 V, respectively, indicating the presence of pseudocapacitance caused by the Faraday reaction. Furthermore, calculations show that the integral area of the CV curve for CHPC-IPF at a ratio of 1.7:1 is the largest, indicating that the average capacitance is highest when the ratio of biochar to fluorinated asphalt is 1.7:1.
[0044] The galvanostatic charge-discharge (GCD) curve of the CHPC-IPF material is as follows: Figure 4 As shown in (b), it can be seen that within the potential window range of -1.2 V to 0.6 V, 0.5 A·g -1 At the given current density, the charge-discharge curve is not ideally linear, which further confirms that a Faraday reaction occurs during these processes.
[0045] Figure 4 (c) shows the Nyquist plot of the CHPC-IPF composite material. The CHPC-IPF 1.7:1 Nyquist plot has the shortest semicircle diameter and the smallest x-coordinate at its intersection point on the real axis, i.e., R. ct and R s The lowest resistance. The lower the resistance, the stronger the conductivity of the sample. This material further reduces the internal resistance and improves the electron conduction path, thereby effectively promoting rapid charge transfer.
[0046] Figure 4 Figure (d) shows the CHPC-IPF material in the range of 0.5–20 A·g. -1 Specific capacitance at current density: the general trend of the sample specific capacitance is that it decreases with increasing current density. Among them, CHPC-IPF1.7:1 exhibits high specific capacitance and good rate performance at 0.5 A·g. -1 The specific capacitance is 372.35 F·g. -1 In 20 A·g -1 The time was 124.48 F·g -1 .
[0047] In summary, the corn cob graded porous carbon composite material prepared through Examples 1-5 has excellent energy storage capacity and can provide sufficient energy even under high power output conditions to meet the application needs of high energy demand scenarios.
[0048] It should be noted that the above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is impossible to exhaustively list all possible implementations here. All obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a fluorine-containing biochar composite material, characterized by, The preparation method comprises the following steps: (1) pretreating the corncob raw material, cutting the corncob into small pieces, performing ultrasonic cleaning, then drying, crushing, passing through a 100-mesh screen, and screening to obtain corncob powder; (2) performing high-temperature pre-carbonization on the corncob powder obtained in step (1), and taking out after cooling, to obtain corncob biochar; (3) mixing the corncob biochar in step (2) with KOH in a proportion, performing high-temperature activation, taking out after cooling, neutralizing the obtained biochar material, repeatedly washing, and finally drying to obtain corncob hierarchical porous carbon material; (4) performing high-temperature vacuum sublimation reaction on a certain amount of fluoride, and sublimation gas covers the surface of the biochar after condensation to obtain a fluorine-containing biochar composite material.
2. The method of claim 1, wherein the fluorine-containing biochar composite is prepared by the steps of: a) mixing a biochar with a fluorine-containing compound; b) heating the mixture to a temperature of 300-600°C; and c) cooling the mixture to room temperature. In step (2), the pre-carbonization conditions are as follows: the heating rate is 1-15 ℃ / min, the pre-carbonization temperature is 600-800 ℃, and the pre-carbonization time is 30-120 min.
3. The method of claim 1, wherein the fluorine-containing biochar composite is prepared by the steps of: a) mixing a biochar with a fluorine-containing compound; b) heating the mixture to a temperature of 300-600°C; and c) cooling the mixture to room temperature. In step (3), the mass ratio of KOH to corncob biochar is 0.3-3:
1.
4. The method of claim 1, wherein the fluorine-containing biochar composite is prepared by the steps of: a) mixing a biochar with a fluorine-containing compound; b) heating the mixture to a temperature of 300-600°C; and c) cooling the mixture to room temperature. In step (3), the activation conditions are as follows: the heating rate is 1-15 ℃ / min, the activation temperature is 550-850 ℃, and the activation time is 30-120 min.
5. The method of claim 1, wherein the fluorine-containing biochar composite is prepared by the steps of: a) mixing a biochar with a fluorine-containing compound; b) heating the mixture to a temperature of 300-600 °C; and c) cooling the mixture to room temperature. In step (4), the fluoride is fluorinated carbon or fluorinated pitch, and the fluorination conditions are as follows: the fluorination temperature is 380-758 ℃, and the fluorination time is 5-20 min. The mass ratio of corncob hierarchical porous biochar to fluoride is 1-1.9:
1.
6. A fluorine-containing biochar composite material prepared by the preparation method according to any one of claims 1-5.
7. A method for producing an electrode material, characterized by, The preparation method comprises the following steps: The fluorine-containing biochar composite material, acetylene black and polyvinylidene fluoride solution are weighed according to a mass ratio of 8:1:1, the fluorine-containing biochar composite material and acetylene black are added into anhydrous ethanol and ultrasonically mixed, then the PVDF solution is added and ultrasonically mixed, then the sample sheet is drop-coated on the nickel foam, the sample sheet is dried, then is pressed into a uniform and flat sheet, and finally an electrode with a fluorine-containing biochar composite material mass ratio of 80% is prepared.
8. The method of claim 7, wherein the electrode material is prepared by a process comprising: The polyvinylidene fluoride solution refers to polyvinylidene fluoride fully dissolved in N-methyl pyrrolidone.
9. An electrode material prepared by the preparation method according to claim 7 or 8.
10. Use of an electrode material as claimed in claim 9, characterized in that The electrode according to claim 7 or 8 is used as a working electrode to construct a supercapacitor.